STUDY ON THE MORPHOMETRIC AND MERISTIC CHARACTERISTICS OF SPLENDID SILVER BELLY- LEIOGNATHUS SPLENDENS (CUVIER) FROM BOMBAY COAST - GULATI, DEEPAK; ACHARYA, P. (Journal of Indian Fisheries Association, 2015)
Ten morphometric and six meristic characters of Leiognathus splendens. (Cuvier) of Bombay Coast have been studied sexwise. Regression and sexwise difference if any between the compared morphometirc characteristics have been worked out. Range, mode, standard deviation, co-efficient of variation of 6 meristic characters have been analysed. The was no significant difference between the sexes in morphometric and any deviation in the meristic characters. Keywords : Silves bellies, Morphometry, Bombay Coast.